Transcriptome and Metabolome Analyses Provide Insights into the Occurrence of Peel Roughing Disorder on Satsuma Mandarin (Citrus unshiu Marc.) Fruit - Lu, Xiao-Peng; Li, Fei-Fei; Xiong, Jiang; Cao, Xiong-Jun; Ma, Xiao-Chuan; Zhang, Zi-Mu; Cao, Shang-Yin; Xie, Shen-Xi (Frontiers in Plant Science, 2017)
Roughing disorder (RD) is a significant quality barrier in citrus fruit, prevalent on easy-peeling mandarins. As RD is not yet well-understood, this study aimed to examine the changes and synergic molecular processes involved in peel RD. Peel with RD was induced by severely defruiting Satsuma mandarin trees. Morphology observations, RNA-sequencing, and targeted and untargeted metabolic analyses were conducted. The results showed that the primary metabolites of sugars, organic acids and amino acids are dramatically changed in RD peel. The RD peel was always characterized by higher magnesium content during development. Comparative transcriptome profiling was performed for CK and RD peels at 30, 80, and 170 days after full bloom (DAFB) which represented fruit at cell division stage, cell enlargement stage and fruit maturity stage, respectively. Physiological and molecular biological evidence suggested that the month after full bloom is a crucial stage for RD initiation. A total of 4,855 differentially expressed genes (DEGs) in RD peel, relative to CK peel were detected at cell division stage, about 2 to 4-fold more than other stages had. Among the differentially expressed transcription factors, the bHLH family were affected most by RD, and six bHLH transcription factors functionally involved in GA metabolism were assessed to associate with RD occurrence. Gene set enrichment analysis suggested that RD significantly altered starch and GA metabolism in peel. Higher starch content and hydrolysed chain status were found in RD peel at cell division stage. RD occurrence on the peel was influenced significantly by GA, especially abundant GA before July. These changes may mean a significant alteration in sink strength of RD peel. The findings of this study provide insights into the emergence, development and molecular mechanisms of RD.